Brevard S. Childs: Kanon, metode og teologi - Poulsen, Frederik (Dansk Teologisk Tidsskrift, 2010)
The article offers an introduction to the work and program of the Old Testament scholar and theologian, Brevard S. Childs. Central to his argument is the emphasis on canon as a rule of faith in the shaping of the biblical literature within the community of faith and practice. In his major work, Biblical Theology of the Old and New Testaments, Childs attempts to establish a theological stance from which the entire Bible can be read in the light of Jesus Christ.